Application of Human Plasma/Serum to Cell Culture In Vitro: A Translational Research Approach to Better Define Disease Mechanisms - Enis Cela; Eric K. Patterson; Sean E. Gill; Gediminas Cepinskas; Douglas D. Fraser (Clinical and Translational Science)
ABSTRACT In vitro cell culture experiments play an important role in medical research. Various cellular mechanisms and signaling pathways have been identified with in vitro experimental techniques. Unfortunately, the clinical and translational impact of these studies is often limited due to their inability to closely resemble physiological or pathophysiological milieus in cell culture and the use of unrealistic experimental conditions. Thus, further developments must be made to improve the translation of in vitro cell culture work. The application of human plasma or serum as a stimulus for cells, human or otherwise, is a relatively new approach that ultimately overcomes many of the in vitro limitations and provides a more physiologically relevant model. While this technique has been used for the investigation of various diseases and pharmacological mechanisms, discrepancies remain regarding the appropriate methodologies. This review provides insight into recent findings through the application of human plasma or serum as stimuli, as well as an analysis of methodological considerations and suggestions for future directions.